What I love about you [large type] - Gibson, Rachel (Center Point Large Print, 2015)
"Former SEAL Blake Junger bought a remote cabin in Truly, Idaho, for the solitude to struggle with his demons--and win. But his neighbor, Natalie Cooper, who moved back to Truly after her now ex-husband took all their money and ran off with a twenty-year-old, is proving to be quite a distraction"--